Modification of piston skirt design - Ahmad Shahril Ashraf, Mohamed (2008)
Piston skirt wear is one of the main failure mechanisms affecting the life of automotive engines. Wear occur during operation because insufficient of lubricant oil in cylinder, over heat, connecting-rod non-alignment and other possible cause. At higher temperature the friction will increase because the piston skirt will expand. This friction can produce wear and scratch at piston skirt. The increase the friction will decrease effect the power output. The objectives of this project; is to design the new piston skirt can stand with high temperature and also can reduce the friction between piston skirt and cylinder wall. The scope of this project is to simulate the original piston skirt using SolidWork software, design three alternative piston skirt designs and to analyze and simulate the new design using Finite Element Analysis (FEA) software known as ALGOR software for failure analysis. From the calculation, the average temperature in combustion chamber is about 548 °C. Design - Three is proved to be the best alternative design with the modulus elastic of 2.62 x 109 N/rn2 . It is observed that at the original piston, high stress exist at the rib and curve of the piston and also high friction occur. In all alternative design piston skirt, the design has minimized the rib and curve at all piston skirt to reduce stress and this will also to reduce friction between piston skirt and cylinder wall.